Effects of melatonin on noncardiogenic pulmonary edema secondary to adnexial ischemia-reperfusion in guinea pig - Celik, H; Ayar, A; Tug, N; Simsek, M; Ozercan, I; Cikim, G; Bildirici, I (Maghira & Maas Publications, 2002)
OBJECTIVES: Pulmonary edema has been shown to occur following ischemia-reperfusion injury in a variety of organs and effects of several pharmacological agents on ischemia-reperfusion-induced damage has been investigated previously. However, there are only a few studies in the literature about pulmonary injury following adnexial ischemia-reperfusion. In this study we aimed at investigating pulmonary changes following adnexial ischemia-reperfusion and the effects of melatonin on noncardiogenic pulmonary edema secondary to adnexial ischemia-reperfusion. METHODS: A total of 32 Dunkin-Harley guinea pigs were randomly divided into four groups. In group 1, oopherectomy was performed following adnexial torsion of three hours (ischemia). Adnexial torsion of three hours followed by a 3 hours detorsion period (reperfusion) and then oopherectomy was performed in remaining three groups. No therapy was given in group one and two while isotonic saline and melatonin was applied intraperitoneally in groups three and four, respectively Serum malondialdehyde (MDA) levels of operated ovaries and lungs and polimorphonuclear leucocyte infiltration of lungs were determined. RESULTS: MDA levels in serum, ovary and lungs were higher in detorsion groups (groups IT, III) than torsion group (group 1) (p < 0.01). Melatonin administration significantly decreased the polimorphonuclear leukocytes infiltration of lung parenchime and MDA levels in serum, ovaries and lungs (groups 11 and TV; groups III and IV; p < 0.01, p < 0.01). MDA levels and lung tissue PNL infiltration levels of melatonin administered detorsioned group was similar to those levels of only salphingo-oopherectomy performed group (Group I and IV, P > 0.05). CONCLUSION: Pathophysiology of ischemia-reperfusion must be considered in the cases of adnexial torsion where detorsion is thought. As an antioxidant, melatonin administration might be helpfull in decreasing post-operative morbidity by decreasing reperfusion injury of lungs.
Keywords: melatonin; ischemia-reperfusion; pulmonary edema; guinea pig